Harmonization of Local Government and Village Authorities and Business Actors’ Legal Responsibilities in Waste Management Based on the West Aceh Regency Waste Management Master Plan (RISPS) - Kurdi Kurdi (JURNAL MERCATORIA, 2026)
Waste management issues in West Aceh Regency indicate the need for harmonization of authority between local governments and village governments, as well as stronger business actors’ responsibilities in establishing a sustainable waste management system. This study aims to analyze the legal status of the Waste Management Master Plan (Rencana Induk Sistem Pengelolaan Sampah/RISPS) of West Aceh Regency within the regional legal framework and to examine the legal responsibilities of local governments, village governments, and business actors in waste management. This research employs a normative legal method using statute, conceptual, and analytical approaches. Primary, secondary, and tertiary legal materials were analyzed qualitatively through a prescriptive method using grammatical, systematic, and teleological interpretations. The findings reveal that RISPS, enacted through a Regent Regulation, functions as a strategic policy instrument that is administratively binding; however, its effectiveness depends on integration into regional development planning and budgeting documents. The harmonization of authority between regency and village governments can be realized through the principles of recognition and subsidiarity, while business actors’ responsibilities should be strengthened through the implementation of the Extended Producer Responsibility (EPR) principle. The novelty of this study lies in the formulation of an intergovernmental authority harmonization model that integrates RISPS with producer responsibility mechanisms within the framework of good environmental governance. Therefore, strengthening regional regulations, integrating RISPS into regional development planning documents, and developing more effective EPR mechanisms are essential to support sustainable waste management.